HUBUNGAN BERAT BADAN DAN PANJANG BADAN LAHIR DENGAN KEJADIAN STUNTING ANAK 12-59 BULAN - Antun Rahmadi (Jurnal Kesehatan Metro Sai Wawai, 2016)
The results of the Nutrition Status Monitoring survey in Lampung Province in 2015 showed that the prevalence of stunting 0-59 months old children was 23%. This figure according to the World Bank (2006) included in the category of moderate public health problems. The purpose of this study was to determine the relationship between body weight and length of birth with stunting incidence in children aged 12-59 months in Lampung Province in 2015. This study used a cross sectional design. The research data is sourced from PSG survey results of Lampung Province in 2015. The samples analyzed are all children aged 12-59 months, which amounted to 3,129 people. Data analysis using bivariate analysis with kai square test. The results showed that the prevalence of stunting amounted to 26.7%. There is a relationship between the length of the birth body and the incidence of stunting, while the LBW is not related to the incidence of stunting in children aged 12-59 months in Lampung Province in 2015. The importance of increasing monitoring efforts of infant growth, especially infants with short birth length with weighing and infant and maternal nutrition .